The Medical Humanities in the Faculties of Medicines: an international perspective - Giarelli, Guido (Medicina e Morale, 2020)
This paper aims to show the origin and evolution of the Medical Humanities at an international level both in a spatial and temporal sense, with the purpose of showing how what is defined as 'Medical Humanities' does not constitute a static field, but is the result of a process of cultural diffusion in which the expansion of the spatial dimension from North America to Europe and subsequently to the other continents coincided with a significant evolution in terms of time, which entailed the attribution of different meanings to this field of studies of multi- or interdisciplinary nature.